Low Vision Accessibility in Structural Equation Modeling Software. Issue 1 (2nd January 2020) - McCabe, Kira O.
Abstract : The purpose of this review is to explore the low vision accessibility features of software packages commonly used for structural equation modeling (SEM). The benefits of including accessibility features can extend well beyond the scope of helping users with disabilities, such as making classroom demonstrations or figures easier to read. This review evaluates four different programs: Mplus, STATA, AMOS (and SPSS), and R (and RStudio). While most of these programs do provide some accessibility features that are helpful for low vision users, there are areas where all these programs could be improved.